Diastereoselective synthesis of highly substituted, amino- and pyrrolidino-tetrahydrofurans as lead-like molecular scaffolds - Moody, Christopher J.; Wales, Steven M.; Merisor, Elena; Adcock, Holly; Pearce, Christopher A.; Strutt, Ian; Lewis, William; Hamza, Daniel (Wiley, 2018)
A series of highly substituted tetrahydrofurans (THFs), decorated with modifiable 2‐aryl, 3‐carboxy and 4‐amino substituents, has been prepared for biological evaluation within the European Lead Factory. Diastereoselective reductive amination of pre‐functionalised 4‐oxofurans, readily prepared from cinnamate esters via oxa Michael/Dieckmann annulation, provided the requisite THF cores on gram scale with three contiguous stereocentres, including full substitution at C‐3. In a second series, a pyrrolidine ring was fused to the same oxofuran scaffold via an intramolecular reductive amination, inverting the configuration at C‐4 relative to the other ring substituents. The resulting compounds, which displayed desirable physical properties as lead‐like scaffolds, were derivatised into a small library of 24 compounds, demonstrating their ability to serve as starting points for drug discovery. Ultimately, this chemistry enabled the preparation of 1948 THF‐containing compounds for inclusion in the Joint European Compound Library.